X(4x-3)=63

Simple and best practice solution for X(4x-3)=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(4x-3)=63 equation:



X(4X-3)=63
We move all terms to the left:
X(4X-3)-(63)=0
We multiply parentheses
4X^2-3X-63=0
a = 4; b = -3; c = -63;
Δ = b2-4ac
Δ = -32-4·4·(-63)
Δ = 1017
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1017}=\sqrt{9*113}=\sqrt{9}*\sqrt{113}=3\sqrt{113}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-3\sqrt{113}}{2*4}=\frac{3-3\sqrt{113}}{8} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+3\sqrt{113}}{2*4}=\frac{3+3\sqrt{113}}{8} $

See similar equations:

| 7-6x+11=5x+18-11x | | 1+a+15=37 | | 5(x-2)+14=3(x+12) | | 8x-50+(3x+10)=180 | | 13t+25=41,9 | | 2x+8+x=2x+15= | | 6(10-3x)=-120 | | 3x+3/3=5x | | 5m-12,7=13,8 | | 3x+3=5x*3 | | 9(j−84)=90 | | x2+x=90 | | -17c-10=-7c+20 | | 24(2x+6)=6(4x+36) | | p+116=7 | | x2+x3+x=90 | | 3x+6-8x=20-5x | | 5z-46=114 | | 8)-3(4r-8)=-36 | | 6k+5=41 | | -15(x-3)=-120 | | -8=w/2+2 | | 2g+5=-9 | | 10(v+6)=9 | | j2+ 13=16 | | 12=4-2a | | 5x-46=66 | | 9=-3+3w | | 6X-8=-4x+7x= | | 3(g2+2)=(3g-2) | | 2x+175=10×-9 | | -6=4+p/3 |

Equations solver categories